PELATIHAN PEMROGRAMAN PEMESINAN CNC BERBASIS SOFTWARE CAM UNTUK MENINGKATKAN KOMPETENSI PADA MAHASISWA PENS SURABAYA - Indrawan, Rizal (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
CNC (Computer Numerical Control) machines are computer-controlled machines to perform various manufacturing processes such as cutting, milling, turning, drilling, and other precision machining. CNC machines enable the production of products more efficiently, accurately, and consistently than manual processes. CNC machines require a program to run the movements in each machining process, and this program is known as CAM (Computer Aided Manufacturing). In this training, the Sotfware used is Master CAM X5. This software makes it possible to draw products and create CAM programs that will later be applied to CNC machines. This training covers from making product designs to making CAM programs with participants from Surabaya State Electronic Polytechnic Students. This training aims to improve student competence in manufacturing. Keywords: Product Design, CNC Machine, CAM Software